Band gap tuning of lanthanum-doped CUSCN via chemical wet process in enhancing HTL for PSC - Mohd Rahim, Farah Liyana (2025)
Perovskite Solar Cells (PSCs) have become one of the most intriguing topics in the avant-garde renewable energy due to their remarkable Power Conversion Efficiency (PCE). Hole Transport Layer (HTL) remains indispensable in all PSCs architectures as it extracts holes from the perovskite layer and subsequently transports to the electrodes while enriching contacts with other layers of the cell. Copper(I) thiocyanate (CuSCN) has garnered attention as an effective HTL in PSCs due to its advantageous electronic properties, high stability, and excellent hole mobility. Unlike the widely used Spiro-OMeTAD, which is sensitive to moisture and degrades rapidly, CuSCN offers a more stable alternative with excellent moisture resistance. CuSCN is particularly promising as it provides a robust interface with better resistance against environmental factors such as moisture, thereby enhancing the overall durability of solar cells without sacrificing efficiency. However, CuSCN's application is limited by its low hole concentration and conductivity. The CuSCN HTL still suffers from the chemical reaction at the interface, predominantly due to copper vacancies. This research introduces Lanthanum (La), a rare earth material, as a dopant that incorporates into CuSCN and acts as HTL in PSCs. The solution-processable deposition of CuSCN using dimethyl sulfoxide (DMSO) facilitates the formation of a highly transparent and stable HTL, crucial for efficient hole extraction and device durability. Experimental optimization identified an optimal La doping concentration of 3 mol%, which yielded a conductivity of 4.13 S/cm, a band gap energy of 3.67 eV, a crystallite size of 8.47 nm, a grain size of 572.50 nm, and a transmittance exceeding 40% at 500 nm of wavelength, indicating sufficient optical transparency for effective light harvesting. These parameters indicate improved charge transport and film quality, which are essential for high-performance PSCs. Using the SCAPS-1D simulation tool, the study further modeled the La-doped CuSCN-based PSC incorporating the experimentally derived parameters. MAPbI₃ (methylammonium lead iodide) was used as the absorber layer, TiO₂ (titanium dioxide) as ETL, Indium Tin Oxide (ITO), and gold as front and back contact. From the simulation, the fully optimized device structure, ITO/TiO₂/MAPbI₃/La-doped CuSCN/Au, attained remarkable PCE of 30.39%, with a fill factor (FF) of 83.63%, short-circuit current density (Jsc) of 25.163 mA/cm², and open-circuit voltage (Voc) of 1.2629 V. Additionally, the simulation explored the influence of various factors such as HTL thickness, doping density, interface defect density, and operating temperature on device performance, allowing for comprehensive optimization. Overall, this work demonstrates that La doping in CuSCN significantly enhances the electrical and interfacial properties of the HTL, leading to improved PSC efficiency and stability